New Horizons in Standardized Work - Martin, Timothy; Bell, Jeffrey (Productivity Press, 2017)
Enabling management to verify that processes are being performed correctly and in an efficient manner, standardized work provides limitless opportunities for process improvements. So much so, that it has become a vital component of improvement efforts in Lean enterprise systems.New Horizons in Standardized Work: Techniques for Manufacturing and Bus.